2018
DOI: 10.2298/csis180322008k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effectiveness of a teaching approach using barker or Bachman notation for conceptual database design

Abstract: Relational databases are one of the pillars of information systems and as a consequence conceptual and logical design can be seen as the foundation of almost every application regardless of the platform. Nevertheless, little research has been done so far on the effectiveness of teaching approaches to database basic concepts and design. This paper introduces a multi-level experimental study developed to examine the effectiveness of learning database fundamentals, depending on the notation used for conceptual de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Kamišalić et al [21] examine the effectiveness of learning conceptual database design. They found that the manual transformation from a conceptual model to a logical data model can increase students' understanding of the concept.…”
Section: B Related Researchmentioning
confidence: 99%
“…Kamišalić et al [21] examine the effectiveness of learning conceptual database design. They found that the manual transformation from a conceptual model to a logical data model can increase students' understanding of the concept.…”
Section: B Related Researchmentioning
confidence: 99%
“…In our previous studies, we examined the effectiveness of learning database fundamentals, depending on the notation used for conceptual design [8]. A multi-level experimental study was set up.…”
Section: Introductionmentioning
confidence: 99%